(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
High-School Moment (Gimnazijski trenutak) is the first collection of poems by Gordana R. Todorović (1933–1979), a forgotten Serbian woman poet who wrote in the period of neo-symbolism and neo-Byzantinism, leaving behind three hundred poems and a thousand neologisms. The collection was published in 1954, by the publishing house Novo pokolenje, and the following year it received Branko’s Prize. By inspecting the reception of this work at the time of its creation and conducting a (post) structuralist analysis of the collection, by defining the scope of its themes and motifs, its lyric subject, verse, stanza and rhyme, and by dealing with its neologisms, this paper re-examines the emergence of High-School Moment in Serbian poetry – the significance and value of this collection in the opus of Gordana R. Todorović and in the history of Serbian literature.